Paraoxonase lactonase activity, inflammation and antioxidant status in plasma of patients with type 1 diabetes mellitus - Savu, Octavian; Serafinceanu, Cristian; Grajdeanu, Ioana Veronica; Iosif, Liviu; Gaman, Laura; Stoian, Irina (Journal of international medical research, 2014)
Objectives To investigate paraoxonase-1 (PON1) lactonase activity, myeloperoxidase (MPO) activity (as a marker of inflammation) and antioxidant status in plasma of patients with type 1 diabetes mellitus. Methods Whole blood and plasma samples were collected from patients with diabetes and healthy control subjects. PON1 lactonase and MPO activities and total antioxidant capacity (TEAC) were determined in plasma. Glycosylated haemoglobin (HbA1c) was quantified in whole blood. Results Plasma PON1 lactonase and MPO activities were significantly higher and TEAC was significantly lower in patients with diabetes (n = 18) compared with healthy control subjects (n = 20). There were significant positive correlations between PON1 lactonase activity and MPO activity and HbA1c level, and plasma MPO and HbA1c. There were significant negative correlations between PON1 lactonase activity and TEAC, and MPO activity and TEAC. Conclusions Increased lactonase activity may inefficiently compensate for the high level of chronic inflammation and low antioxidant capacity in the plasma of patients with type 1 diabetes mellitus.